Interplay between components of a novel LIM kinase–slingshot phosphatase complex regulates cofilin - Soosairajah, Juliana (2005)
Slingshot (SSH) phosphatases and LIM kinases (LIMK) regulate actin dynamics via a reversible phosphorylation (inactivation) of serine 3 in actin-depolymerizing factor (ADF) and cofilin. Here we demonstrate that a multi-protein complex consisting of SSH-1L, LIMK1, actin, and the scaffolding protein, 14-3-3ζ, is involved, along with the kinase, PAK4, in the regulation of ADF/cofilin activity. Endogenous LIMK1 and SSH-1L interact in vitro and co-localize in vivo, and this interaction results in dephosphorylation and downregulation of LIMK1 activity. We also show that the phosphatase activity of purified SSH-1L is F-actin dependent and is negatively regulated via phosphorylation by PAK4. 14-3-3ζ binds to phosphorylated slingshot, decreases the amount of slingshot that co-sediments with F-actin, but does not alter slingshot activity. Here we define a novel ADF/cofilin phosphoregulatory complex and suggest a new mechanism for the regulation of ADF/cofilin activity in mediating changes to the actin cytoskeleton.